Biomarkers associated with the diagnosis and prognosis of Mycoplasma pneumoniae pneumonia in children: a review - Ding, Lele; Jiang, Yonghong (Frontiers in Cellular and Infection Microbiology, 2025)
Community-acquired pneumonia (CAP) is a major cause of death in children, and Mycoplasma pneumoniae (MP) is the main pathogen of CAP in children in China. Although Mycoplasma pneumoniae pneumonia (MPP) is usually a self-limiting disease, many children develop multiple complications due to drug resistance or untimely diagnosis and treatment, and may even progress to severe MPP or refractory MPP with a poor prognosis. It is important to explore the value of biomarkers that can be used in clinical practice to assess the severity of pneumonia and assist in clinical decision making. In this article, we searched the literature in the last four years to review the roles of various types of biomarkers in MPP and the associated clinical predictive models, with the aim of helping pediatricians to understand the evaluation indexes related to MPP in children other than microbiology.